Model of Islamic Religious Education for Children in Indonesia Minority Muslim Families - Purwanto, Purwanto; Aryanti, Yosi; Susanti, Weti (STIT Ahlussunnah Bukittinggi, 2022)
This research aims to find out the form of Islamic religious education in Muslim families in Pasakiat Taileleu Village, then to find out the implementation of Islamic religious education in Muslim families in Pasakiat Taileleu Village and to find out the opportunities and challenges in the implementation of Islamic religious education in Muslim families in Pasakiat Taileleu Village. This research uses a descriptive qualitative approach. Data collection techniques: observation, interview, and documentation with data analysis through data reduction, data presentation, and conclusion drawing and verification. The results of this research analysis show that the Islamic religious education model in Pasakiat Taileleu Village includes a model of cultivating awareness, omission, wisdom, interaction, commands and prohibitions, advice, habits, punishment, and reward. The implementation of Islamic religious education in Muslim families in this village includes faith education tauhid, worship education, and moral education. Among the three types of education, the most prioritized is faith education because Muslims in this village are a Christian minority. The opportunities for implementing Islamic religious education in this village are the example of parents, the availability of parental time, the existence of Islamic religious education institutions, support from immigrants, the minimal influence of social media, the presence of preachers who serve, and peaceful social conditions. Meanwhile, the challenges in implementing Islamic religious education in this village are the majority Christian environment, the large number of tourists who come to travel, the parents' lack of knowledge about religion, poor economic conditions, limited religious information, and the lack of religious figures. The results of this research can provide guidance for minority Muslim families and perhaps also in other places, and can be used as initial data for future researchers in studying this problem in different contexts and issues.